(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
• Introduction Missed appointments and poor adherence to scheduled clinic visits remain significant barriers to efficient healthcare delivery in outpatient settings. Appointment systems are designed to optimize patient flow, minimize wait times, and improve patient satisfaction, but their effectiveness is often undermined by patients’ knowledge and attitudes. This is particularly relevant in tertiary health institutions where patient load is high and resource planning is critical. Objective This study assessed the level of compliance with the appointment system among patients attending outpatient clinics at the University College Hospital (UCH), Ibadan. It also examined the relationship between respondents’ knowledge of the appointment system and their attitudes, and explored factors influencing appointment adherence. Method of Data Analysis A descriptive cross-sectional study was conducted among 160 outpatients selected using a systematic sampling technique. Data were collected through a structured questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. Descriptive statistics such as frequencies and percentages summarized the data, while Chi-square tests were used to determine the association between knowledge levels and patients’ attitudes. Statistical significance was set at p<0.05. Result Most respondents (95%) adhered to their scheduled appointments, and 87.5% reported arriving before their scheduled time. Despite this, 37.5% admitted to occasionally visiting outside their appointment dates, citing complaints and emergencies as major reasons. Rescheduling was experienced by 39.4% of patients, largely due to public holidays and health worker strikes. Statistically significant associations were found between good knowledge of the appointment system and positive attitudinal indicators, such as arriving early (p=0.008), remembering appointment dates (p=0.022), and not missing appointments due to social (p=0.002) or religious (p=0.010) obligations. Conclusion The findings underscore the critical role of patient knowledge in promoting adherence to outpatient appointment systems. Although compliance is high at UCH, Ibadan, there is a need for targeted educational interventions and institutional improvements to address systemic challenges and sustain patient engagement. Enhancing knowledge and refining scheduling processes could significantly improve healthcare efficiency and patient satisfaction.